Linking ecosystem services with epibenthic biodiversity change following installation of offshore wind farms - Causon, Paul D.; Gill, Andrew B. (Elsevier, 2018)
The growing awareness of climate change and the recognised need to secure energy production has been a driving force behind the expansion of the offshore wind industry across the world. Benefits from offshore wind farms (OWFs) may extend further than low CO2 energy production. Wind turbine substructures introduce hard surfaces that are rapidly colonised by epibenthic marine organisms, altering biomass and biodiversity within the local ecosystem. Biodiversity plays a critical role in supporting ecosystem processes and functions that maintain ecosystem services. As offshore wind development continues to grow and modify marine habitats, changes in biodiversity could affect the provision of ecosystem services. In this context, this review sets out to capture the current understanding of epibenthic biodiversity change following the installation of OWFs and attempt to link these changes in biodiversity with marine ecosystem services through the associated processes and functions.
Keywords: Benthic ecology; Biodiversity; Biofouling; Ecosystem services; Epibenthic colonisation; Offshore wind farms